Efficacy of Solvent Type on Antioxidant Activity of Artocarpus heterophyllus Leaves Extract: A Scoping Review - Ida Bagus Ideyogiswara; Bagus Komang Satriyasa; Agung Nova Mahendra; Agung Wiwiek Indrayani; Ketut Agus Adrianta (Indonesian Journal of Global Health Research, 2026)
Jackfruit leaves (Artocarpus heterophyllus) contain various bioactive compounds that have the potential as natural antioxidants. The antioxidant activity of jackfruit leaf extract is influenced by the type of solvent used during the extraction process. Objective to identify the effectiveness of various types of solvents on the antioxidant activity of jackfruit leaf extract. This study used a scoping review method by reviewing articles from PubMed, ScienceDirect, and Google Scholar in 2020–2025 Searching strategy using the keywords "Artocarpus heterophyllus" OR "jackfruit leaves" AND "antioxidant activity" OR "antioxidant capacity" AND solvent OR "solvent type" OR "extraction solvent" . Included articles were English-language primary studies published between 2020 and 2025. A total of 11 articles that met the inclusion criteria were analyzed descriptively. The data were analyzed descriptively and presented in tabular form to identify patterns of findings related to the effectiveness of various solvent types on the antioxidant activity of Artocarpus heterophyllus leaf extrac. Ethanol and hydroethanol solvents showed higher antioxidant activity than other solvents. Strong antioxidant activity is related to the high content of phenolic and flavonoid compounds that were successfully extracted. The type of solvent affects the antioxidant activity of jackfruit leaf extract, with ethanol and hydroethanol being the most effective solvents in extracting bioactive antioxidant compounds.